Differential sandwich theorems for p-valent functions defined by convolution involving certain fractional derivative operator (مجلة العلوم الإنسانية والتطبيقية, 2017)
In the present paper, we derive some subordination and superordination results for p-valent functions in the open unit disk defined by convolution involving certain fractional derivative operator. Relevant connections of the results, which are presented in the paper, with various known results are also considered.